Selection of intermediate routes for secure data communication systems using graph theory application and grey wolf optimization algorithm in MANETs. Issue 5 (5th May 2021) - Balaji, Subbiah; Obaidat, Mohammad S.; Suthir, Sriram; Rajesh, Manoharan; Suresh, Koneri Chandrasekaran
Abstract: A mobile ad hoc network consists of set of mobile nodes and communication devices to interact without any support of the infrastructure. Unlike wired networks, the challenges faced in mobile ad hoc networks possessed such as security design, network infrastructure, stringent energy resources and network security issues. The need for these security issues is much focused in overcoming the challenges in MANET. The proposed work focuses on the secure communication using a novel approach addressed on radio station problem for route optimization, which is deployed by grey wolf optimization (GWO) algorithm and supportively Task Based Admittance Control Model is proposed to monitor the network flow and to identify the malicious nodes. It is also called as role‐based control model. The communication is performed based on the cluster of vast sizes these trusted in node(s) will probably be conveying together, at the same time non ‐entry correspondence of the non‐authorized node(s) to keep on maintaining a stable, anchored, and reliable gathering of mobile nodes. Simulation is performed using network simulator where the network parameters such as throughput, packet delivery ratio, and delay and packet loss are analyzed to identify the malicious nodes.